Analysis of Competence and Service Quality on Customer Satisfaction and Loyalty in Eastern Indonesia Border Tourism - Milcha Handayani Tammubua; Deni Surapto (Budapest International Research and Critics University, 2021)
The border tourism between Indonesia and Papua New Guinea is currently in great demand by many tourists. Therefore, this study aims to analyze customer satisfaction and loyalty which are influenced by competence and service quality. To test the direct and indirect effect hypothesis, this study adopts a quantitative research approach. The research instrument used was a questionnaire. The sample of this research was 192 tourists who were visiting the PLBN Skouw tour. The research data were analyzed using Partial Least Squares (PLS) analysis method with SmartPLS3.0 software. The results of this study can prove that competence can have a positive and significant effect on service quality and customer satisfaction. Customer satisfaction has a positive and significant effect on customer satisfaction and loyalty. In addition, customer satisfaction can also mediate the relationship between competence and customer satisfaction. Customer satisfaction is proven to have a positive and significant effect on customer loyalty. Customer satisfaction can also mediate the relationship between service quality and customer loyalty.